Evaluation Of Heat Shock Protein-27 Levels as A Predictor of Diabetic Nephropathy in Early Diabetics - Muhammad Irfan; Shabir Ahmed; Adil Ramzan; Nosheen Wasee; Nuvair Zia; Nargis Anjum (KARACHI MEDICAL AND DENTAL COLLEGE, 2021)
Objective: The current study objective is to find out the levels of heat shock protein-27 in diabetes patients with and without diabetic nephropathy, and to appraise the functional role of HSP-27 as an early diagnostic biomarker in progressive diabetic nephropathy. Study Design: Case control study. Place and Duration of Study:  The current study was conducted in physiology department, Basic Medical Science Institute (BMSI), Jinnah Post-Graduate Medical Center (JPMC), Karachi from March 2019 to September 2020. Methodology: A total 105 participants between 30-50 years of age were separated into three groups: Group A (n=35) diabetic-patients with history of diabetes < 5 years without any sign of DN; Group B (n=35) diabetic patients with history of diabetes >5 years duration of diabetes and microalbumin levels < 30 mg/dl in urine and Group C (n=35) healthy individuals. All this study participants were gone through detailed history, anthropometric measurement, BMI, serum blood sugar, serum urea, serum creatinine, BUN, urinary albumin, and serum HSP-27 were estimated. Results: Elevated levels of HSP-27 were seen in group-A patients as compared to group-C (p<0.001). Elevated levels of HSP-27 were presented in group-B as compared with group-C (p<0.001) which signify early renal parenchyma injury. Strong association had been seen for HSP-27 with creatinine (r=0.69; p < 0.001), and HbA1c (r =0.72; p <0.001) and urea (r = 0.72; p <0.001) in all these participants. While statistical highly significant and strong positive association were reported for HSP-27 with microalbumin (r = 0.86; p< 0.001) in all participants. Conclusion: Elevated levels of HSP-27 with progression of renal injury with or without declining of renal function is seen in current study. These findings perhaps suggest and recognizing HSP-27 as key diagnostic marker for diabetic nephropathy in early diabetics. KEYWORDS: Diabetes Mellitus, Diabetic Nephropathy, HSP-27.